Transforming 2D children's painting into 3D public art for improving public spaces towards people's happiness - Luo, Na (2024)
COVID-19 has caused a large part of the population to suffer depression, hence there is a need for cities to provide mass relief to the public. This thesis formulates a process to transform 2D children’s painting into 3D public art in order to help artists produce more quality public arts for cities. The objective of this study is to enhance the quality of urban public spaces to boost people's happiness by transforming 2D children's paintings into 3D public art. This study reviewed extensive literature, focusing on the relationship between children's paintings and public art and people's happiness as well as the principles of public art creation. This study posits that applying the visual characteristics found in 2D children's painting can support its transformation into 3D public art suitable for urban public space which can help boost people's happiness. A case study and in-depth interviews with 7 public arts’ artists were conducted to develop a workflow for 3D public art creation with children's paintings as the feature. Then, three public arts were created according to the workflow, namely "Colourful Shadow Print", "Rainbow Swing", and "The Harvest of Happiness". Finally, a statistical analysis on a survey conducted using a questionnaire found that over 90% of people believe that public art featuring children's paintings in public spaces can alleviate people's mental stress, enhance their leisure experience, and boost sense of happiness. Applying the visual characteristics of 2D children's painting (rich and high-purity colours, simple and general shape, free and random composition) can support transformation into 3D public art (publicity, interaction, innovation) suitable for urban public space (urban culture, enhance the urban image) which helps to improve people's happiness. In conclusion, this study contributes in developing a methodology for transforming 2D children's paintings into 3D public art. Furthermore, this study also encourages Chinese artists to create more public art for urban public spaces that meets people's aesthetic needs. Besides supporting fellow artists to earn more public commissions, public arts located in urban spaces suit people's aesthetic needs, relieve people's stress, and enhance their leisure experience, thereby able to evoke a sense of well-being.